Genetic mechanism of heat stress tolerance at anthesis among three different rice varieties with different fertilities under heat stress - Takai, Toshiyuki; Lumanglas, Patrick; Simon, Eliza V. (Informa UK Limited, 2020)
The enhancement of heat stress tolerance at anthesis is an important strategy to achieve sustainable rice production in the context of predicted global warming. In this study, we genetically analysed spikelet fertility under high temperature treatment (38°C) at anthesis using the three rice varieties, namely, Koshihikari and Takanari, which were developed in Japan, and IR64, which was developed in the Philippines. Genetic analysis of the F2 population between Takanari and IR64 revealed a quantitative trait locus (QTL) on chromosome 4 that increased spikelet fertility with the Takanari allele and that was likely qHTSF4.1, a previously fine-mapped major QTL. Genetic analysis using chromosome segment substitution lines (CSSLs) carrying Koshihikari chromosome segments in the IR64 genetic background did not show any QTLs. In contrast, genetic analysis using CSSLs carrying Koshihikari chromosome segments in the Takanari genetic background revealed some QTLs, including chromosomes 4 and 9. These results suggest that the expression of QTLs may depend on genetic background. The two CSSLs, SL1313 and SL1330, which carried the QTLs on chromosomes 4 and 9, respectively, exhibited a spikelet fertility of over 80% and relatively large anther dehiscence compared with Takanari. These results suggest that the Koshihikari allele of QTLs may be related to improved anther dehiscence, which may lead to successful pollination and ultimately increased spikelet fertility under heat stress conditions. The findings in the present study should be useful to enhance heat stress tolerance at anthesis in rice in future breeding programs.